The design and implementation of an ORM-based information warehouse - Chau, Vo Thi Ngoc; Chittayasothorn, Suphamit (My University, 2005)
Since 1995, star schema has been popularly utilized to represent warehouse data at the logical level. Information warehouse design mainly focuses on the design of a warehouse star schema. There are many proposals on conceptual data warehouse design of a star schema based on some well-known data models such as the Entity Relationship Model (ERM), and an extension to the Unified Modeling Language (UML). This paper presents the design and implementation of an information warehouse using the Object Role Model (ORM) as the data model both for user modeling of the warehouse and for the underlying implementation model of the system. A warehouse multi-star/star schema is automatically generated from the input schema description based on ORM using a deep-structured natural language interface. Users input simple English sentences together with the structured sections for type declarations and constraints on these sentences. Since the input ORM schema can also be transformed into 5NF operational relational schemas, this system allows warehouse users to generate star schemas from their operational schemas.